Understanding Gender Disparities in Quality of Life Among Patients With Type 2 Diabetes in Ethiopia: An Institutional‐Based Study - Enguday Demeke Gebeyaw; Girma Deshimo Lema (Lifestyle Medicine, 2025)
Abstract Introduction Health‐related quality of life (HRQoL) is a multidimensional concept that reflects an individual's perception of their overall health. In Ethiopia, research on diabetes has generally focused on the clinical aspects of the disease, such as glucose control, medication, and complications. However, social factors like gender have not been given a focus. This study aimed to assess gender differences in HRQoL and identify gender‐specific factors contributing to poor HRQoL. Research Design and Methods A cross‐sectional study was conducted among 380 type 2 diabetes mellitus patients (190 males and 190 females) at Debre Berhan public hospitals from January 1 to March 30, 2024. HRQoL was measured using the revised version diabetic‐specific quality of life questionnaire (RV‐DQoL13) scale. Chi‐squared tests were utilized to analyze gender differences in HRQoL, while logistic regression was employed to identify gender‐specific factors influencing HRQoL. A significant association was declared at a p‐value less than 0.05. Results Female patients reported significantly poorer HRQoL than their male counterparts. From HRQoL domains, women reported higher levels of worry and lower satisfaction scores, whereas men had higher impact scores. Among males, factors associated with poor HRQoL included age > 60 years, lower educational status, and diabetes complications, whereas being privately employed was related to better HRQoL. For females, lower educational status, duration of diabetes > 5 years and diabetes complications were significant determinants of poor HRQoL, while being married and having a normal body mass index were associated with better HRQoL. Conclusion Gender differences in HRQoL among type 2 diabetes patients at Debre Berhan public hospitals are influenced by a complex interplay of sociodemographic, behavioral, and clinical variables. The study highlights the need for considering both gender‐specific and general factors when assessing HRQoL. Healthcare professionals may need to adopt gender‐sensitive healthcare practices to address the unique needs of men and women.